Pengaruh Corporate Social Responsibility, Executive Characteristic, Family Ownership, Profitabilitas dan Corporate Governance Terhadap Tax Aggressiveness - Putri, Shara Amelia; Nasruddin (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study aims to analyze the effect of corporate social responsibility disclosure, executive characteristics, family ownership, profitability, corporate governance toward tax aggressiveness. Corporate governance is proxied with institutional ownership, the size of the board of commissioners and the audit committee on tax aggressiveness. The research data uses the companies’ annual financial statements during the period 2017-2021. The data were analyzed by using multiple linear regression. The result of the research indicates that the exposure of corporate social responsibility and the size of the board of commissioners have a negative effect on tax aggressiveness, executive characteristics and independent commissioners have no effect on tax aggressiveness, while family ownership, profitability and audit committee have a positive effect on tax aggressiveness.